Monitoring and Evaluating Rainfall–Runoff Control Effects of a Low Impact Development System in Future Science Park of Beijing. (29th June 2021) - Shen, Hongbin; Xu, Zongxue
Abstract: Monitoring and evaluating on rainfall–runoff control effects are important in low impact development (LID) practices. This is mainly done for different individual LID facility at microscales; however, some LID systems comprise multiple facilities within a large‐scale area. Here, the Future Science Park (FSP) of Beijing City was selected as the study area. The rainfall–runoff control effects of an LID system are monitored and examined, including not only the rainfall volume capture effect but also the rainfall control mode, which is influenced by the confluence relationship. The confluence relationship between an impervious surface and LID facility can be manifest as a series or as parallel systems. When rainfall is less than the water quality capture volume, rainfall control operates in event‐capture mode for a series system and in partial‐capture mode for a parallel system. A series system is more suitable for water quality improvement and peak flow reduction. The results for the FSP indicated that the rainfall volume capture effect was acceptable; the average runoff coefficient of 16 rainfall events was about 0.10. However, rainfall control operated in a partial‐capture mode. For individual rainfall events smaller than the designed rainfall, small amounts of runoff were generated mainly by the impermeable road network. In future, the impermeable roads and green belt areas alongside the roads should include a series confluence to improve rainfall–runoff control effects. Abstract : Research Impact Statement : Rainfall–runoff control effects of an LID system comprising multiple facilities within a large area are monitored and evaluated, that is helpful for the development of LID practices.